Molecular mechanisms for pharmacological effects of drugs based on Cimicifuga racemosa extracts - O A Gromova; I Yu Torshin; N K Tetruashvili; L E Fedotova; N P Lapochkina (IP Berlin A.V., 2018)
An estrogen-like activity is considered to be the main mechanism of action for Cimicifuga extract. At the same time, results of modern studies of molecular composition together with modern fundamental data indicate such critical mechanisms of action as activation of serotoninergic and GABA-ergic ways of neurotransmission, as well as anti-inflammatory and antidiabetic effects. The use of drugs based on C. racemosa extracts is perspective for accompanying replacement hormonal therapy with estrogens due to antineoplastic and osteoprotective effects of standardized C. racemosa extracts.